A comprehensive review on the role of co-signaling receptors and Treg homeostasis in autoimmunity and tumor immunity. (December 2018) - Kumar, Prabhakaran; Bhattacharya, Palash; Prabhakar, Bellur S.
Abstract: The immune system ensures optimum T-effector (Teff) immune responses against invading microbes and tumor antigens while preventing inappropriate autoimmune responses against self-antigens with the help of T-regulatory (Treg) cells. Thus, Treg and Teff cells help maintain immune homeostasis through mutual regulation. While Tregs can contribute to tumor immune evasion by suppressing anti-tumor Teff response, loss of Treg function can result in Teff responses against self-antigens leading to autoimmune disease. Thus, loss of homeostatic balance between Teff/Treg cells is often associated with both cancer and autoimmunity. Co-stimulatory and co-inhibitory receptors, collectively known as co-signaling receptors, play an indispensable role in the regulation of Teff and Treg cell expansion and function and thus play critical roles in modulating autoimmune and anti-tumor immune responses. Over the past three decades, considerable efforts have been made to understand the biology of co-signaling receptors and their role in immune homeostasis. Mutations in co-inhibitory receptors such as CTLA4 and PD1 are associated with Treg dysfunction, and autoimmune diseases in mice and humans. On the other hand, growing tumors evade immune surveillance by exploiting co-inhibitory signaling through expression of CTLA4, PD1 and PDL-1. Immune checkpoint blockade (ICB) using anti-CTLA4 and anti-PD1 has drawn considerable attention towards co-signaling receptors in tumor immunology and created renewed interest in studying other co-signaling receptors, which until recently have not been as well studied. In addition to co-inhibitory receptors, co-stimulatory receptors like OX40, GITR and 4-1BB have also been widely implicated in immune homeostasis and T-cell stimulation, and use of agonistic antibodies against OX40, GITR and 4-1BB has been effective in causing tumor regression. Although ICB has seen unprecedented success in cancer treatment, autoimmune adverse events arising from ICB due to loss of Treg homeostasis poses a major obstacle. Herein, we comprehensively review the role of various co-stimulatory and co-inhibitory receptors in Treg biology and immune homeostasis, autoimmunity, and anti-tumor immunity. Furthermore, we discuss the autoimmune adverse events arising upon targeting these co-signaling receptors to augment anti-tumor immune responses. Highlights: The role Immunoglobulin and TNF superfamily co-stimulatory and co-inhibitory molecules on Treg homeostasis are critically reviewed. Effect of loss and gain of co-signaling receptors on Tregs and its correlation to various autoimmune diseases is explained. The role of co-inhibitory receptors andTregs on tumor evasion and use of immune checkpoint inhibitors are discussed. Association between immune checkpoint point blockade and resulting autoimmune adverse events are reviewed.